A QUANTITATIVE ANALYSIS AND COMPARISON OF NITROGEN, PHOSPHORUS AND POTASSIUM IN SOIL AND WATER OF THE WUKARI MUNICIPAL SOLID WASTES NATURAL DRAINAGE - Anongo (now Jeyol), M'ember Catherine; Gangume, C.; Shehu-Ruga, Y. (FUDMA Journal of Sciences, 2023)
Preliminary investigation of Municipal Solid Waste Natural (MSW) drainage for dry season irrigation farming of Amaranths at Angwan Mission Quarters – a densely populated locality known for cultivation of Amaranths due to availability of water and its accessibility to markets was conducted. Amaranths, soil and water samples from three drainage or sampling points was collected (December 2019 - March 2020) to ascertain suitability of drainage soils and water for irrigation of Amaranths. Visual observation and analysis of selected morphological traits (plant colour, plant height (cm), plant girth, leaf area (cm2) and number of leaves) for market value was conducted. Physic-chemical analyses of pH, total organic carbon (C), total organic matter (OM), exchangeable bases (K, Na, Ca, Mg), cation exchange capacity (ECEC), moisture content, total nitrogen (N), phosphorus (P),potassium(K) concentrations of the MSW drainage soils and water were determined according to Standard laboratory procedures. Results reveal chlorosis of Amaranths at sampling point 1(Up-Stream) and sampling point 2(Mid-Stream) indicating specific mineral deficiency (such as Iron, magnesium, nitrogen) usually associated with MSW dumpsites. Significant difference (p<0.05) in whole plant height, leaf area, number of leaves and % nitrogen (Up-Stream - 0.11 ± 0.00a; Mid-Stream - 0.14 ± 0.01a : Low-Stream - 0.16 ± 0.15) reflects abundance water and inadequate nitrogen levels respectively. This study remarked that the drainage points are suitable for dry season vegetable farming and the transition from rural to peri-urban settlement has potentials for continuous utilization of drainage soil and water for large-scale vegetable farming and income generation by the